2020
DOI: 10.1111/idj.12523
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and professional quality of life among Israeli dentists: the role of sensory processing sensitivity

Abstract: Aim Dentistry is a stressful and exhausting profession with high levels of burnout. Sensory processing sensitivity (SPS) is a basic personality trait characterised by a gradient of sensitivity to both internal and external stimuli, including social and emotional cues. In this study, the influence of SPS on burnout and professional quality of life among Israeli dentists was analysed. Methods Two‐hundred and forty‐three Israeli dentists responded to questionnaires that collected information on their SPS and prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 37 publications
5
31
0
1
Order By: Relevance
“…Finally, in view of the influence of compassion satisfaction and high sensitivity on compassion fatigue observed, regardless of sector, the dimensions of sensory processing sensitivity, ease of excitation and aesthetic sensitivity, increased compassion fatigue, while the effect of compassion satisfaction reduced compassion fatigue. These findings enable us to confirm that sensory processing sensitivity is a factor influencing quality of life of care professionals [ 36 ]. Our results report on a high percentage of professionals with compassion fatigue, predicted by ease of excitation and aesthetic sensitivity.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Finally, in view of the influence of compassion satisfaction and high sensitivity on compassion fatigue observed, regardless of sector, the dimensions of sensory processing sensitivity, ease of excitation and aesthetic sensitivity, increased compassion fatigue, while the effect of compassion satisfaction reduced compassion fatigue. These findings enable us to confirm that sensory processing sensitivity is a factor influencing quality of life of care professionals [ 36 ]. Our results report on a high percentage of professionals with compassion fatigue, predicted by ease of excitation and aesthetic sensitivity.…”
Section: Discussionsupporting
confidence: 68%
“…From the results found, emotional exhaustion was observed to be reduced in both sectors with increased compassion satisfaction, while the increase in ease of excitation would contribute to increasing emotional exhaustion, with compassion satisfaction having a larger effect size. In agreement with these results, some authors [ 36 ] have found that ease of excitation predicts the reaction to stress, whereas others [ 8 ] have found that higher compassion satisfaction could predict less emotional exhaustion.…”
Section: Discussionsupporting
confidence: 58%
“…A recent survey by Toon et.al of 1513 dentists in the UK found statistically significant relationship (p<0.01, β=0.67) between work related stress and burnout in UK dentists amongst other factors [7]. Research in other parts of the world have highlighted similar findings over the last two decades [8,9]. OH can provide timely intervention for fitness to continue working by suggesting restrictions/adjustments, referral to employee assistance programme to access counselling services and ongoing review [10].…”
Section: Discussionmentioning
confidence: 87%
“…Predominant characteristics of high SPS individuals (e.g., Aron, 1996Aron, , 2004Aron, , 2011 run counter to broader social discourses around wellbeing that dominate WEIRD cultures such as Australia. Indeed, SPS typically is portrayed as a negative characteristic that sets individuals up for a range of illbeing outcomes (e.g., Bakker & Moulding, 2012;Booth et al, 2015;Listou Grimen & Diseth, 2016;Meyerson, Gelkopf, Eli, & Uziel, 2019). Yet despite this misfit, some high-SPS individuals do experience high levels of wellbeing (Black & Kern, 2020;Sobocko & Zelenski, 2015).…”
Section: Discussionmentioning
confidence: 99%